Sosialisasi Pendidikan Inklusif Pada Guru-Guru PAUD di Kabupaten Tasikmalaya - N. Dede Khoeriah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2017)
Inclusive education is a strategy to improve the education system through policy changes and exclusive implementation. Inclusive education sets children as the center of study, flexible and able to accept differences in the characteristics and background of every child to live with, and focus on how to minimize and eliminate the various barriers of access, participation and learning for all children, especially for those who are socially discriminated as a result of disability and disorder. This is the first step to further promo tea more tolerant, peaceful, and democratic life. To support the approach of inclusive education, socializationis an on going activity that should be implemented invarious levels of education, family, play, work and society.